Imagining Afghanistan Global Fiction and Film of the 9/11 Wars - Ivanchikova, Alla (Comparative Cultural Studies, 2019)
What do we imagine Afghanistan to be? The Ruins of Kabul examines how the meaning of "Afghanistan" has been produced, ordered, and perpetuated through literary and visual texts that were published after the 9/11 attacks and the subsequent U.S.-led invasion-the era that propelled Afghanistan into the center of global media visibility. Through an analysis of fiction, graphic novels, memoirs, plays, and film, the book demonstrates that writing and screening Afghanistan has become a tool for understanding our shared post- 9/11 condition-a hermeneutics of the contemporary.